2013
DOI: 10.1155/2013/132642
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Marrow-Derived Mesenchymal Stem Cells for Organ Repair

Abstract: Mesenchymal stem cells (MSCs) are prototypical adult stem cells with the capacity for self-renewal and differentiation with a broad tissue distribution. MSCs not only differentiate into types of cells of mesodermal lineage but also into endodermal and ectodermal lineages such as bone, fat, cartilage and cardiomyocytes, endothelial cells, lung epithelial cells, hepatocytes, neurons, and pancreatic islets. MSCs have been identified as an adherent, fibroblast-like population and can be isolated from different adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 111 publications
4
87
0
Order By: Relevance
“…91,92 Besides BM, MSCs can be isolated from adipose tissues, lung, gingiva, placenta, liver, cord blood, and umbilical cord. [93][94][95][96] There are some similar experiments showing that MSCs from the other tissues also can polarize macrophages to the alternatively activated M2 phenotype. In parallel observation with human placental MSCs, Abumaree et al 97 also found that the human placental MSCs also have potent anti-inflammatory and immunosuppressive actions via converting macrophages from a proinflammatory M1 phenotype to an anti-inflammatory M2 phenotype.…”
mentioning
confidence: 89%
“…91,92 Besides BM, MSCs can be isolated from adipose tissues, lung, gingiva, placenta, liver, cord blood, and umbilical cord. [93][94][95][96] There are some similar experiments showing that MSCs from the other tissues also can polarize macrophages to the alternatively activated M2 phenotype. In parallel observation with human placental MSCs, Abumaree et al 97 also found that the human placental MSCs also have potent anti-inflammatory and immunosuppressive actions via converting macrophages from a proinflammatory M1 phenotype to an anti-inflammatory M2 phenotype.…”
mentioning
confidence: 89%
“…While MSCs have been shown to express other markers and to differentiate into other cell types, such as myocytes, these aspects are not considered requirements to define cells as MSCs (Dimarino et al, 2013). Murine MSCs must fulfil similar criteria, with positive expression of CD106 and Sca1, and the absence of CD45, CD11b and CD31 (Li and Ikehara, 2013).…”
Section: Bone Marrow-derived Mesenchymal Stem Cells and Pericytes -Dementioning
confidence: 99%
“…In addition, MSCs have a role in each of the three-stage injury healing responses (inflammatory, proliferative, and remodeling), and their presence supports healthy physiologic functioning towards successful healing. For example, MSCs regulate immune and inflammatory responses, and possess powerful tissue protective and reparative effects through paracrine signaling by releasing biologically active molecules that affect cell migration, proliferation, and survival/remodeling of the cells surrounding the site of injury [62][63][64][65][66][67].…”
Section: Regenerative Potential Of Mscs and Paracrine Activitiesmentioning
confidence: 99%
“…MSC differentiation contributes by regenerating damaged tissue, whereas MSC paracrine signaling regulates the local cellular responses to injury. Although, the molecular mechanisms of MSCs involvement in healing response are not yet fully understood, MSC paracrine signaling is thought to be the likely primary mechanism for the beneficial effects of MSCs on injury healing, that is, to reduce inflammation, promote angiogenesis, and induce cell migration and proliferation [62][63][64][65][66][67].…”
Section: Regenerative Potential Of Mscs and Paracrine Activitiesmentioning
confidence: 99%